Addressing the Basic Literacy and Numeracy Crisis in Underdeveloped Villages: A Model of Parental and Teacher Facilitation through Local Educational Games - Hanafiah, Hanafiah; Basri, Teuku Hasan; Mendrofa, Netti Kariani; Hafiz, Asnal; Lubis, Tsuwaibatul Aslamiyah (International Journal of Community Service (IJCS), 2025)
This study explores a community-based model to mitigate the crisis of basic literacy and numeracy in underdeveloped rural villages through the collaborative facilitation by parents and teachers using local educational games. Employing a qualitative research methodology, the study analyzes the effectiveness of integrating traditional games in literacy and numeracy development in disadvantaged village settings in Indonesia. Data were collected through interviews, focus groups, and observations involving educators, parents, and village children. Findings indicate that the model fosters increased engagement, comprehension, and supportive learning environments at home and schools. The participatory approach enhances awareness, motivation, and the application of basic numeracy and literacy skills, suggesting a culturally contextualized sustainable strategy for rural education improvement.